Salomon's Sophocracy as a Source of Inspiration for Changing Madagascar's History - Randrialiva Soanirina Seheno; Robijaona Rahelivololoniaina Baholy (Polit Journal Scientific Journal of Politics, 2023)
In the unfolding narrative of Madagascar's post-independence journey, the troubling paradox of economic regression persists amidst the nation's bountiful natural wealth, coveted by others. Despite the implementation of diverse policies by successive leaders, the pervasive specter of poverty endures. This theological contemplation propels a fervent call for a policy metamorphosis—a conscientious exploration of sophocracy, rooted in the wisdom epitomized by King Solomon, as a transformative catalyst. A historical-critical analysis of Solomon's governance, woven from biblical texts and scholarly discourse, reveals sophocracy's potential to restore equilibrium, necessitate substantive reform, and harmoniously integrate with other forms of power. Yet, the theologian's discerning gaze acknowledges the need for an adapted Malagasy sophocracy, cognizant of human vulnerabilities. The prospect emerges that a locally nuanced sophocracy, grounded in Malagasy wisdom and identity, could redefine the nation's history. However, this journey is tempered by a vigilant consideration of internal and external risks, echoing the delicate interplay between divine guidance and human agency.